Inheriting and Buying a Homeland The Land of Israel and the Patriarchs - Cordoni, Constanza 1976- (2018)
After 70 CE, when Israel was no longer an independent nation in the land of Israel and their cultic center was no longer physically present there, the rabbis of the Palestinian and Babylonian diaspora reflect from different perspectives on the beginning of the story of the land, on what can be called the "homeland myth" of the patriarchal narratives of Scripture. In doing so, they create their own ancestral homeland myth. In this article, two sets of rabbinic texts are examined in order to illustrate how the rabbis refashioned the scriptural myth and produced two versions of a rabbinic ancestral homeland myth. The first group of texts are related to the promise of the land and its fulfilment, the second to the establishment of the first Jewish grave in the promised land.
Keywords: Bibel; Land; Erbschaft; Kauf; Patriarch; Diaspora; Homeland; Land of Israel; patriarchal narratives; Rabbinic Literature